An attempt to assess the knowledge of nurses about the scope of professional responsibility under the amended provisions of law– a preliminary report - Gotlib, Joanna; Maliszewska, Agnieszka (Polish Journal of Public Health, 2013)
Introduction. The professional responsibility of nurses is regulated by the Act on Professional Self-Government of Nurses and Midwives of July 1st, 2011. Aim. The aim of this study was to assess the knowledge of nurses about the scope of professional responsibility under the amended provisions of the law. Material and methods. The study involved 73 randomly selected people (71 women) practising as nurses in selected Warsaw hospitals. The mean length of time in professional work amounted to 13 years. Group 1 compri-sed 44 people with a higher education degree. Group 2 comprised 29 people with a secondary school certificate. Voluntary and anonymous questionnaire study using a questionnaire developed by the authors, 22 questions. Results. The level of knowledge of nurses about their professional responsibility was insufficient and required supplementation. The degree of education did not influence the level of knowledge. Statistically significant differences between the study groups were observed only in the case of civil and professional responsibility (p<0.001). Conclusions. 1. The knowledge of nurses from the study group about the provisions of law regulating their professional responsibility was insufficient and required supplementation. 2. In the study group, the degree of education did not influence the knowledge of nurses on the scope of professional responsibility. 3. There is a need to constantly update the knowledge of nurses on legal issues regarding their profession and professional responsibility since this knowledge is essential for correct and safe performance of professional activities